Potentialities and Challenges of Using Internet and Digital Technologies in Teaching Learning Activities - Jnawali, Laxman (Bhairahawa Campus Journal, 2023)
The internet and the digital technologies are modern technological devices which have been very useful for the modern human beings. This article does constructive analysis of the usefulness of internet and digital technologies in the field of teaching and learning. This article is a systematic review that follows content analysis of the different national and international level articles which deal regarding the issues of the challenges and opportunities of the digital devices in the field of teaching learning activities. The themes which have been explored from the review of the literature have been thoroughly analyzed in logical and argumentative way. They have been systematically organized for the sake of generating new knowledge. The article comes to an end with results and findings in the conclusion section along with some recommendations of the researcher.